2011
DOI: 10.1177/0143034311406821
|View full text |Cite
|
Sign up to set email alerts
|

The study of externalizing and internalizing behaviours in Greek, Russian, Indian, and Chinese children using the Fairy Tale Test

Abstract: The present study investigated externalizing and internalizing behaviours in Greek (n = 599), Russian (n = 596), Indian (n = 571), and Chinese (n = 376) 7- to-12-year-old children. The Fairy Tale Test was used to measure impulsive and motivated aggression, fear of aggression, anxiety, and depression. The results indicated culture-specific patterns of the aforementioned behaviours. Greek children demonstrated the highest levels of impulsive and motivated aggression, while Russian children had the highest fear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
0
21
0
2
Order By: Relevance
“…However, it also revealed some cultural distinctiveness, the most common type of aggressive behavior for example, as well as the meaning and the justification for the use of aggressive behavior (Severance et al, 2013). Savina, Coulacoglou, Sanyal, and Zhang (2011) suggested that children's externalizing and internalizing problems also have some specific cultural features. Findings from DR Congo, Ethopia and Nigeria showed that externalizing problems such as conduct disorder, antisocial disorder and hyperactivity are also a common phenomenon in Sub-Saharan Africa (Adelekan, Ndom, Ekpo, & Oluboka, 1999;Ashenafi, Kebede, Desta, & Alem, 2001;Kashala, Elgen, Sommerfelt, & Tylleskar, 2005).…”
Section: Externalizing Problems In Low-income Countriesmentioning
confidence: 99%
“…However, it also revealed some cultural distinctiveness, the most common type of aggressive behavior for example, as well as the meaning and the justification for the use of aggressive behavior (Severance et al, 2013). Savina, Coulacoglou, Sanyal, and Zhang (2011) suggested that children's externalizing and internalizing problems also have some specific cultural features. Findings from DR Congo, Ethopia and Nigeria showed that externalizing problems such as conduct disorder, antisocial disorder and hyperactivity are also a common phenomenon in Sub-Saharan Africa (Adelekan, Ndom, Ekpo, & Oluboka, 1999;Ashenafi, Kebede, Desta, & Alem, 2001;Kashala, Elgen, Sommerfelt, & Tylleskar, 2005).…”
Section: Externalizing Problems In Low-income Countriesmentioning
confidence: 99%
“…Experiencing emotional states such as anxiety and depression is a universal phenomenon (Spielberger, 2006) reported internationally in children and adolescents in various countries including Australia, India, Greece, Russia, and China (Neil & Christensen, 2009; Sahoo & Khess, 2010; Savina, Coulacoglou, Sanyal, & Jhang, 2011; Tully, Zajac, & Venning, 2009). For example, Shin (2010) reports that 41% of the 80,000 Korean children completing a web-based survey experienced depressive affect.…”
mentioning
confidence: 99%
“…In most societies girls tend to score higher on internalizing kinds of problems, especially at ages 12- to 16-years-old and boys on externalizing kinds of problems, especially at ages 6- to 11-years-old (Crijnen et al., 1997; Rescorla et al., 2007a). There are also culture-specific patterns of internalizing and externalizing problems (Savina, Coulacoglou, Sanyal, & Zhang, 2012). In the school environment, externalizing problems are more apparent than internalizing problems.…”
mentioning
confidence: 99%